Deremenda Y. M. Foreign borrowings in ergonymy (based on company names of the Ternopil region) - Deremenda Y. M. (Philological Treatises, 2020)
The present article studies the state of vocabulary of company names of the Ternopil region formed with the use of foreign borrowing. It defines the source languages for company names of the Ternopil region and lays out the percentage of each of them. Semantic and associative mechanisms of advertising effect of borrowing, as well as forms of graphic representation of foreign borrowings in company names of the Ternopil region are studied.